Islamic Religious Education in Student Character Development - K, Munawir; Rahim, Abdul; Ismawati, Ismawati; Mutmainna, Fadliatun (Al-Hayat: Journal of Islamic Education, 2024)
This article aims to analyze students' character development in learning Islamic education and character, describing supporting and inhibiting factors as well as solutions. This type of research is descriptive qualitative research using phenomenological and pedagogical approaches. The data collection techniques used were observation, interviews and documentation at the research location at UPT SD Negeri 1 Tamalatea. Data validity using triangulation. Data analysis techniques consist of data reduction, data presentation, and conclusion. The research results show that the form of character building for students in learning Islamic education and character is that the teacher provides a good example, instils Islamic religious values and character in students, and gives assignments as an evaluation. Supporting factors include adequate facilities and infrastructure and cooperation with parents while inhibiting factors include environmental factors and the influence of technology. The solution to this problem is for the school to provide advice, apply applicable regulations, and provide sanctions. This research provides knowledge about the correlation between subjects and educational goals in character development. Using this model, educational purposes can be achieved according to expectations, especially in student character or manners.